How french teacher's associated factors (academic studies, methodology and personality) influence the academic performance of students from the major of Modern Languages of the 2nd year of the University of El Salvador, during the semester I-2013 by the time they take Intensive French III - Ramos Aguilar, Ana Carolina; Sánchez Peña, Rocío Azucena; Gamero Ortiz, José Ricardo; Ayala, Edgar Nicolas (San Savador, El Salvador : Universidad de El Salvador, 2014)
The present research begins with the premise that French teacher‟s associated factors such as: academic studies, methodology, and personality are important in the performance of students from the Foreign Language Department. Therefore this study comprehends a mixed-approach research which includes the implementation of both: qualitative and quantitative approaches. However, the primordial base of this investigation is qualitative method, provided that quantitative approach only helps to complement the study. For instance, the researchers made use of different kind of data gathering instruments which are designed in order to answer the research questions. The instruments which support the investigation are: questionnaires, in-depth interviews, non-participant observations. Another section of the research is related to data collection which is analyzed in two stages. The first stage consists on the statistical analysis of questionnaires, quantitative analysis; on the other hand, the second stage is based on the analysis of each qualitative instrument. Finally, the investigation presents the main findings, the stipulated conclusions, and some recommendations that the researchers took into account as a result of the complete mixed-approach method.
Tesis para optar al título de -- (Licenciada en Lenguas Modernas Especialidad en Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2014
Bibliografía : hoja 88
Keywords: Francés; Rendimiento académico; Lenguas romances